Outreach on Drug Rehabilitation for Minors Outside the Courts in Pari Village, Pantai Cermin District, Serdang Bedagai Regency - Maysarah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Drug abuse among minors is a serious problem with broad impacts on the health, social well-being, and future of the younger generation. This program aims to raise public awareness about the importance of rehabilitation for juvenile drug users outside the courts, particularly in Pari Village, Pantai Cermin District, Serdang Bedagai Regency. Through outreach, counseling, and education activities, the community is provided with an understanding of the mechanisms of medical and social rehabilitation as mandated by Law Number 35 of 2009 concerning Narcotics and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This program also encourages the implementation of the principle of diversion so that child drug abusers are not treated as perpetrators of crimes, but rather as victims in need of recovery. The results of the activities indicate an increase in the understanding of the community and village officials regarding the importance of rehabilitation and support for the